Quantitative evaluation of reactive oxygen and chlorine species generated by discharge in PBS. (2nd October 2019) - Honda, Ryosuke; Sasaki, Shota; Takashima, Keisuke; Sato, Takehiko; Kaneko, Toshiro
Abstract: While plasma devices delivering combined stimuli such as electric current and reactive species to biological tissues are promising medical tools, improvements in invasiveness and controllability are required for practical use. We herein demonstrated stable discharge generation in phosphate-buffered saline using thin ( φ 2.2 mm) and bendable cable without working gas supply toward the combination use with endoscope proposed as less invasive surgery. The discharge generated H2 O2, OH, and ClO − /HClO in accordance with the discharge duration, whereas only electric current treatment without the discharge generated relatively low level of ClO − /HClO. In particular, the increase rate of the ClO − /HClO generation to the discharge duration was lower than that of H2 O2 generation, showing the potential of the generation ratio control of ClO − /HClO as RCS (reactive chlorine species) to H2 O2 as ROS (reactive oxygen species).